Probiotic effects of mixture of Groenewaldozyma salmanticensis and Gluconacetobacter liquefaciens on growth and immune responses in Paralichthys olivaceus. (1st June 2020) - Rhee, C.; Kim, H.; Emmanuel, S.A.; Kim, H.‐G.; Won, S.; Bae, J.; Bai, S.C.; Koh, S.‐C.
Abstract: This study was performed to evaluate the effects of dietary probiotics on growth, non‐specific immune responses and disease resistance in olive flounder, Paralichthys olivaceus. During 8 weeks, the fish were fed the five experimental diets such as a basal commercial diet (CON), oxytetracycline (OTC) and three basal diets containing Bacillus subtilis (BS), a commercial microbial product (CES) and a mixture of yeast and bacterium (PI), respectively. Fish fed all the probiotics diets and OTC showed a significantly higher growth than fish‐fed CON ( P < 0·05). Fish‐fed PI had a significantly higher nitroblue tetrazolium activity, whereas fish‐fed CES showed a higher lysozyme level ( P < 0·05). A 7‐day challenge test also showed that fish‐fed PI had a cumulative survival rate equivalent to that of fish‐fed OTC ( P < 0·05). Moreover, the diet (PI) appeared to increase the diversity of microbial community in the fish. All these results suggest that the probiotics diet could function as a potential antibiotic replacer in the olive flounder. Significance and Impact of the Study: This study is unique in revealing that a diet mixture of yeast, Groenewaldozyma salmanticensis and bacterium Gluconacetobacter liquefaciens can enhance growth, innate immunity and diversity of microbial community including dominant species in the olive flounder. All these indicate that the diet mixture could function as a potential antibiotic replacer in one of the most commercially important fisheries in South Korea.